Does Minimum Wage Increase Labor Productivity? Evidence from Piece Rate Workers - Hyejin Ku (Institute of Labor Economics (IZA), 2020)
We examine worker effort as a potential margin of adjustment to a minimum wage hike using unique data on piece rate workers who perform a homogenous task and whose individual output is rigorously recorded. By employing a difference-in-differences strategy that exploits the increase in Florida's minimum wage from 6.79 to 7.21 on January 1, 2009, and worker location on the pre-2009 productivity distribution, we provide evidence consistent with incumbent workers' positive effort responses.
Keywords: J20; J38; M50; 330; minimum wage; incentive; effort; labor productivity